2018
DOI: 10.3390/math6100204
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Comparisons and Dynamic Information of Random Lifetimes in a Replacement Model

Abstract: We consider a suitable replacement model for random lifetimes, in which at a fixed time an item is replaced by another one having the same age but different lifetime distribution. We focus first on stochastic comparisons between the involved random lifetimes, in order to assess conditions leading to an improvement of the system. Attention is also given to the relative ratio of improvement, which is proposed as a suitable index finalized to measure the goodness of the replacement procedure. Finally, we provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…It is worth pointing out that the latter relation is in agreement with the result provided in Proposition 2 of [3].…”
Section: Remarksupporting
confidence: 91%
See 2 more Smart Citations
“…It is worth pointing out that the latter relation is in agreement with the result provided in Proposition 2 of [3].…”
Section: Remarksupporting
confidence: 91%
“…Less attention has been devoted to the cases when the uncertainty is related to the previous status of the system. Within such framework, in this paper we continued the study of a replacement model considered in [3]. In the previous paper, the replacement is planned in advance, the replaced item possessing a different failure distribution and having the same age of the replaced item.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the methods developed in order for degradation data analysis are becoming typical tools over the last decades. The analysis of degradation data is possible after setting the definition of lifetime (see, e.g, Di Crescenzo and Di Gironimo [15], Guo and Lee [16], Lee et al [17], and Liu et al [18]).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [18] showed that the system performance is better (worse) with the stronger component heterogeneity in the parallel (series) system under the usual stochastic order and the (reversed) hazard rate order under the conditions of interdependency and independency. Also, Di Crescenzo et al [19] gave results for stochastic comparisons of random lifetimes in a replacement model.…”
Section: Introductionmentioning
confidence: 99%